2019
DOI: 10.26873/svr-545-2018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Stem Cell Aging

Abstract: The aging of multicellular organisms is a complex process, which is a result of various mutually complementary causes. One of these causes is the aging of stem cells. The biological function of stem cells is the replacement of cells that are lost due to illness, injury or normal fluctuations in the maintenance of tissue homeostasis. Molecular mechanisms involved in stem cell aging are similar to those involved in the aging of somatic cells. They include DNA damage and mutations, cell senescence, stem cell exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It was previously shown that old bone marrow (BM) cells have a lower proliferative capacity [ 5 , 8 ], resulting in a lower cell density in the HSC niche. In our study, this was confirmed after two and three weeks of culturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that old bone marrow (BM) cells have a lower proliferative capacity [ 5 , 8 ], resulting in a lower cell density in the HSC niche. In our study, this was confirmed after two and three weeks of culturing.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, (g) changes in metabolism and nutrient sensing occur, where signaling pathways involved in anabolic processes accelerate the aging of HSCs. Intrinsic cellular alterations have been extensively reviewed in several studies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The aging process is a dynamic, time-dependent process characterized by the gradual, ever-increasing cell damage, the progressive reduction of cell functions, and the increased susceptibility to morbidity (Valavanidis et al, 2012 ). Although aging is a relatively well-preserved process among all organisms, the underlying molecular mechanisms differ between species and are still an active field of investigation (Xu and Tahara, 2013 ; Deschênes and Chabot, 2017 ; Magalhães et al, 2018 ; Jazbec et al, 2019 ; Warraich et al, 2020 ). Both genetic and environmental factors seem to variably contribute to the aging process, with environmental factors being major contributors (Kirkwood, 2005a ).…”
Section: Introductionmentioning
confidence: 99%